PHONEMIC REPETITION AS A STYLISTIC DEVICE IN LINGUISTIC STRUCTURES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of alliteration of phonemes, focusing on its linguistic mechanics, emotional resonance, and cultural significance. Phonemes, the smallest units of sound in a language, form the foundation of alliteration, which involves the repetition of these sounds to create rhythm, emphasis, and memorability. The discussion highlights the diverse applications of alliteration, from its historical use in oral traditions like Anglo-Saxon and Norse poetry to its modern-day prevalence in branding, advertising, and popular media. The article also delves into the psychology of alliteration, emphasizing how repetition aids cognitive processing and enhances recall. By categorizing alliteration into consonantal and vocalic forms, and examining its connection to phonetic features like articulation and emotional impact, the piece provides a detailed framework for understanding and employing this technique effectively. Ultimately, the article positions alliteration as both an artistic and functional tool in language, underscoring its timeless relevance and versatility. It invites readers to appreciate the beauty of repeated sounds and consider their power in shaping communication and thought.